Low cost diffuser based micropump using pinch actuation - Chee, Pei Song; Ruzairi, Abdul Rahim; Uda, Hashim, Prof. Dr.; Rashidah, Arsat; Leow, Pei Ling (Scientific.net, 2012)
Link to publisher's homepage at http://www.scientific.net/